Strategi Kepemimpinan Kepala Sekolah Dalam Meningkatkan Kinerja Pendidik dan Tenaga Kependidikan di SMA Negeri 1 Kepulauan Sula - Umasangadji, Suhaiba Raudah; Adam, Adiyana (Jurnal Ilmiah Wahana Pendidikan, 2025)
The principal's leadership plays a crucial role in achieving educational objectives, especially in remote areas like SMA Negeri 1 Kepulauan Sula. This study examines the strategies employed by the principal to improve the performance of educators and staff in the school. Using a qualitative descriptive method, data were collected through observations, interviews, and documentation. Findings reveal that the principal implemented strategies such as human resource development aligned with the school's vision and mission, competency enhancement through training and workshops, and motivation-building initiatives. Challenges identified include varying levels of teacher motivation, limited technological skills among staff, and resource constraints. To address these, the principal adopted structured supervisory plans, technology integration, and adaptive approaches to accommodate diverse teacher needs. The study highlights the significant impact of effective leadership on educational quality improvement, suggesting that similar strategies could benefit other schools facing analogous challenges.